English and the Indian short story : essays in criticism - Ramanan, Mohan, 1949-; Sailaja, P. (Pingali), 1962- (Orient Longman Ltd., 2000)
Contributed articles presented at the National Seminar on "English and the Indian Short Story" held in August 1994 at the Dept. of English, University of Hyderabad.